Towards a New Industrial Revolution? Entropy and its Challenges - Bernard Stiegler; Maël Montevil; Victor Chaix; Marie Chollat-Namy; Joel White (Technophany)
This is a transcribed and translated  a podcast of the interview concerning the 1st chapter of the book Biurquer: Il n’y a pas d’alternative [Bifurcate: There Is No Alternative] on the scientific, technological and political stakes of the notion of entropy. The discussion took place between Bernard Stiegler, Maël Montévil, Marie Chollat-Namy and Victor Chaix, on the 1st of July 2020.